ACTR-36. A SINGLE ARM PHASE 2 STUDY OF THE DUAL mTORC1/mTORC2 INHIBITOR VISTUSERTIB PROVIDED ON AN INTERMITTENT SCHEDULE FOR NEUROFIBROMATOSIS 2 PATIENTS WITH PROGRESSIVE OR SYMPTOMATIC MENINGIOMAS. (5th November 2018) - Plotkin, Scott; Jordan, Justin; Beauchamp, Roberta; Muzikansky, Alona; Stemmer-Rachamimov, Anat; Ramesh, Vijaya
Abstract: Meningiomas are the second most common tumor in NF2 patients, with a cumulative prevalence of 80% by age 70 and a high prevalence of multiple meningiomas. Surgery remains standard of care for these tumors, yet outcomes remain suboptimal for many patients with multiple tumors. Loss of NF2 expression is associated with activation of the mTOR pathway, but treatment with the mTORC1 inhibitor everolimus is not associated with tumor shrinkage. We hypothesized that inhibition of both mTORC1 and mTORC2 pathways would result in increased activity against meningiomas. This single center, phase II, open label study evaluated adults (18 years) with NF2 and progressive meningiomas treated with vistusertib. Subjects received vistusertib 125 mg BID two consecutive days per week. Radiographic response was defined as 20% decrease in tumor volume from baseline. The primary endpoint was radiographic response rate in the target meningioma; secondary endpoints included radiographic response in non-target meningiomas and vestibular schwannomas. We enrolled 18 subjects (5M;13F) with a median age of 40 years (range 18–60 years). Baseline volume of target meningioma was 14.2 ml (range, 3.3–69.2 ml) and median pretreatment growth rate was 33%/year. A radiographic response was seen in 1/18 (6%) target meningiomas and in 2/20 (10%) of non-target meningiomas and in 2/21 (9.5%) of vestibular schwannomas. Three target meningiomas (17%) progressed during treatment. Seven subjects (39%) discontinued treatment by choice due to tolerability and 8 remain on study. Adverse events included fatigue, nausea, vomiting, anorexia, rash, mucositis, and hypophosphatemia. Vistusertib treatment is associated with radiographic response rates of 5–10% in meningiomas and schwannomas in NF2 patients, with only a minority of meningiomas progressing during treatment. Grade 2 toxicity led to treatment discontinuation in a significant minority of patients. Future analyses will address the relationship between tumor shrinkage and activation of TORC1/2 pathways in archival tumor specimens.